Glycogen storage disease in two sisters: A case report - Sajal Twanabasu; Prabin Duwadee; Sushan Homagain; Jeevan Ghimire; Ram Chandra Rijal (Clinical Case Reports, 2023)
Key Clinical Message Glycogen storage diseases (GSDs) are rare autosomal disorders that result from defects in glycogen metabolism. There are more than 12 types, each with distinct clinical features. Clinical scenario, biochemical abnormalities are useful for suspicion whereas liver biopsy and enzyme assay provides definite diagnosis. We report a case of two sisters with similar clinical symptoms suggestive of the disease.